Effect of Bakri balloon tamponade on hemorrhage during and after cesarean section in patients with placenta previa - Dongmei Li; Xiaobo He; Hairui Cai; Junjun Zhou (Clinical and Experimental Obstetrics & Gynecology, 2021)
Background: To evaluate the success rate of Bakri balloon tamponade (BBT) and the risk factors for BBT failure in the treatment of intraoperative and postpartum hemorrhage (PPH) in patients with placenta previa. Methods: Patients with placenta previa who underwent cesarean section and had BBT insertion for PPH were consecutively included from 2016 to 2018. Patients with placenta previa who successfully underwent routine insertion of a BBT during cesarean section and had their bleeding controlled were classified as the balloon success group. Patients who successfully underwent BBT during cesarean section but continued to have uncontrolled bleeding were classified as the balloon failure group. Multiple logistic regression was performed to examine the risk factors for BBT failure. Results: During the study, 270 women with placenta previa were identified. The success rate of BBT for managing PPH was 69.3%. The balloon failure group (n = 83) comprised those who had undergone BBT insertion, followed by B-lynch suture (n = 10), uterine artery ascending branch ligation (n = 32), pelvic arterial embolization (n = 21), or cesarean hysterectomy (n = 20). The intraoperative blood loss was 3098 mL (700–18,000 mL) in the balloon failure group and 1120 mL (500–4000 mL) in the balloon success group, respectively (p < 0.01). Multiple logistic regression analysis showed that the number of weeks at pregnancy termination (odds ratio [OR] = 1.188, 95% confidence interval [CI]: 1.023–1.379), the presence of placenta accreta (OR = 2.472, 95% CI: 1.361–4.493), and placenta previa classification (OR = 4.798, 95% CI: 1.328–17.337) were positively associated with BBT failure, while preoperative albumin levels (OR = 0.788, 95% CI: 0.714–0.869) were negatively related to BBT failure. Conclusion: This study suggests that BBT is effective as the second-line treatment for PPH associated with placenta previa in the Chinese population. Placenta accreta and major previa are risk factors for BBT failure. However, our findings need to be confirmed in larger samples with different ethnicities.